Bitter, Sabine y Weber, Helmut (eds.). (2018). Autogestion or Henri Lefebvre in New Belgrade. Berlín: Sternberg Press - Espinosa Zepeda, Horacio (Estudios Demográficos y Urbanos, 2019)
Bitter, Sabine y Weber, Helmut (eds.). (2018). Autogestion or Henri Lefebvre in New Belgrade. Berlín: Sternberg Press